The Effect of HOTS-Oriented Blended Learning Model on Work and Energy Materials Using Google Classroom for Students' Critical Thinking Skill - Qonita Puja Kesuma; Feriansyah Sesunan; Ismu Wahyudi (Physics Education Research Journal, 2022)
This study aims to determine the effect of HOTS-oriented blended learning model student worksheets on work and energy materials assisted by Google Classroom on critical thinking skill. This research was conducted at SMAN 1 Tanjung Bintang using a quasi-experimental form of non-equivalent control group design with purposive sampling technique. The sample of this research is students of grade X MIPA 2 and X MIPA 3. The data were tested by N-gain analysis, independent sample T-test, and Effect size test. The average N-gain in the experimental grade is 0.64 in the medium category. The results of the independent sample T-test showed that there was a difference in the average N-gain of students' critical thinking skill in the experimental grade and the control grade, which showed that the treatment had a significant effect. The magnitude of the effectiveness of using Effect size shows a value (d) of 0.91 with a higher category. The results of the research in the experimental grade showed an increase in students' critical thinking skill that were higher than the control grade, this means that there is an effect using the HOTS-oriented blended learning model worksheet assisted by Google Classroom on improving students' critical thinking skill.